Injury profile in the highest-level rugby union competition in Japan - Takemura, M.; Okayama, A.; Takazawa, Y.; Maruyama, K.; Toyama, M.; Higashihara, J.; Furuya, S. (7th World Congress on Science and Football (WCSF), 2011, 2011)
To collect injury data and describe its characteristics for a certain population is an essential first step for the prevention of sports injuries. The Japan Rugby Top League (JRTL), which was established in 2003, is the highest-level rugby union competition held from September to February in Japan. This study aimed to describe incidence, recurrent rate, severity, and nature of injuries on whole teams involved in a 2-year competition period. Methods A total of 16 teams registered in the league in 2008 and 2009 seasons were studied. Every team doctor, with/without the assistance of athletic trainers, evaluated match injuries and recorded each injury on a questionnaire sheet according to the consensus statement standardized by the Rugby Injury Consensus Group in the IRB. Results & Discussion 222 injuries were documented during the two competitive seasons, showing less injury incidence with 34.3 [95%CI; 29.9-39.1] injuries/1000player-hours than the English professional rugby union1). 19.4% of these injuries were recurrent injuries. Injuries classified as "Mild" indicated the highest (31.1%) of all injuries, and average lost time was 22.0..28.3 days. 94.1% were macrotraumatic injuries, of which "Sprain/ligament injuries" were 27.4%, "Haematoma/contusion/bruise" 16.8%, and"Fracture" 12.0%. Of these macrotraumatic injuries, 44.8% occurred in the "Head/face" and "Knee" nearly equally. Tackle was the most causal playing situation ("Being tackled"; 8.6 [6.5-11.2] injuries/1000player-hours, "Tackling"; 6.6 [4.8-8.9] injuries/1000player-hours), causing 44.6% of the contributing playing situations. The nature of injuries in the current study was similar to those in English Premiership. Injuries related with tackle situations should be analyzed to clarify the causes and preventive approaches. Conclusion Injury incidence tends to be lower in the JRTL than the English Premiership. However, analyzing tackle situations could lead to a lower incidence in rugby union.